# Re: Parametric solutions of Euler Brick?

Proginoskes wrote:
Proginoskes wrote:
Gerry Myerson wrote:
In article <1163021324.077080.226470@xxxxxxxxxxxxxxxxxxxxxxxxxxx>,
"Proginoskes" <CCHeckman@xxxxxxxxx> wrote:

Hauke Reddmann wrote:
Those who don't know what an Euler brick is
(a quader with integer sides and face diagonals -
one with additional space diagonal is still
sought and conjectured to be nonexistent)

I thought nonexistence was proved a couple of years ago, by a student
from Georgia (Georgia Europe, not Georgia USA).

Actually, Georgia, (Western) Asia.

Actually, it was only last year.

----------

"The Diophantine Rectangular Parallelepiped (A Perfect Cuboid)"

Lasha Margishvili

Supervisor: Dr. Mamuka Meskhishvili

Tbilisi, Georgia, 2005

[A proof that there is no Euler Brick, as summarized by C C Heckman.]

[BEGINNING OF PART TWO]

We now consider cases (a)-(d).

If (a) is true, then k^2 = m^2, so we do not have a solution, because
of Proposition 6.

If (b) is true, then k^2 = n^2, so this is not true.

If (c) is true, then k = a^2 (which cannot happen, since then k = m) or

k = a^2 * sqrt((a^4 t^2 - a^8 + t^4) / (a^4 t^2 + a^8 - t^4))

and since m = a^2 and n = t,

k = m * sqrt((m^2 n^2 - m^4 + n^4) / (m^2 n^2 + m^4 - n^4)).

If (d) is true, then k = a^2 (again; this can't happen, since k = n
follows) or

k = n * sqrt((m^2 n^2 - n^4 + m^4) / (m^2 n^2 + n^4 - m^4)).

By symmetry, we only consider the value of k in case (c).

Now, let d = gcd(m,n), and m_1 = m / d, n_1 = n / d.

Proposition 8: The expression

m * sqrt((m^2 n^2 - m^4 + n^4) / (m^2 n^2 + m^4 - n^4))

is integer iff the equation m_1^2 n_1^2 + m_1^4 - n_1^4 = 1 has a
solution, with
m = m_1 d and n = n_1 d, and gcd(m_1,n_1) = 1.

Proof of Prop 8: Since k is an integer, either the expression under the
square root is a perfect (integer) square, or m "must be divided by the
denominator under square root". Since

gcd(m_1, m_1^2 n_1^2 + m_1^4 - n_1^4) = 1,

d^2 must be a multiple of m_1^2 n_1^2 + m_1^4 - n_1^4; then d^4 is a
multiple of
m^2 n^2 + m^4 - n^4. Then we get

m^2 n^2 + m^4 - n^4 = d^4, so
(**) m_1^2 n_1^2 + m_1^4 - n_1^4 = 1.

If the expression under the square root is a perfect square, then

(***) N^2 = (m_1^2 n_1^2 - m_1^4 + n_1^4)
/ (m_1^2 n_1^2 + m_1^4 - n_1^4)

From (***), we get:

m_1^2 n_1^2 (N^2 - 1) = (n_1^4 - m_1^4)(N^2 + 1)

gcd (m_1,n_1) = 1 implies that gcd(m_1^2 n_1^2, n_1^4 - m_1^4) = 1, so

P = (N^2 + 1)/(m_1^2 n_1^2) = (N^2 - 1)/(n_1^4 - m_1^4)

for some positive integer P.

This gives us a system of Diophantine equations:

N^2 + 1 = P(m_1 n_1)^2
N^2 - 1 = P(n_1^4 - m_1^4)

If we subtract the second expression from the first, we get

2 = P [(m_1 n_1)^2 - n_1^4 + m_1^4].

Hence P = 1 or 2.

If P = 1, then m_1^2 n_1^2 + m_1^4 - n_1^4 = 2. If we view this
equation as a quadratic equation in m_1^2, we have

m_1^2 = (-n_1^2 + sqrt(5 n_1^4 + 8))/2

The last digit of 5 n_1^4 + 8 is 3 or 8 (as n_1^4 ends in 0, 1, 5, or
6), which means it can't be a perfect square.

Hence P = 2. Then (**) is true. (End of proof of Prop 8.)

[Section: Fibonacci Enters]

The solutions to (**) are

m_1^2 = F_(2k-1) and n_1^2 = F_(2k),

where F_s is the s-th Fibonacci number. (Proof: _Mathemtical Gems III_,
No 9, 1985, MAA, "A Second Look at the Fibonacci and Lucas Numbers" /
K. R. S. Sastry, "A Fermat-Fibonacci Collaboration", _Crux
Mathematicorum No 5, Vol 23, 1997.)

Furthermore, the only Fibonacci numbers which are perfect squares are
F_0 = 0, F_1 = 1, F_2 = 1, and F_12 = 144. (J. H. E. Cohn, "Square
Fibonacci Numbers, Etc", _Fibonacci Quarterly_, vol 2, 1964, pp.
http://math.asu.edu/~checkman/SquareFibonacci.html ).

Thus m_1 = 1, n_1 = 1, which means m = d = n, contradicting Proposition
6. Consequently, the Diophantine rectangular parallelepiped does not
exist.

[END OF PART TWO]

-------------------

--- Christopher Heckman

.

## Relevant Pages

• Re: Cosmetic opinion, picture link
... Leonardo Pisano is better known by his nickname Fibonacci. ... Liber abaci, published in 1202 after Fibonacci's return to Italy, was ... extremely fruitful and appears in many different areas of mathematics ... nor the square root of a fraction. ...
(sci.med.dentistry)
• Re: Enigma 1395 - A matter of fives
... I have in mind five five-digit numbers. ... perfect square; ... or has both its digits ...
(rec.puzzles)
• Re: No irrationals
... if the radicand is a perfect square, then simplify and you are ... see if the is a perfect square in the radicand. ...
(sci.math)
• Re: Enigma 1395 - A matter of fives
... I have in mind five five-digit numbers. ... perfect square; ... or has both its digits ...
(rec.puzzles)
• Re: Square root algorithms and complexity
... >>> perfect square or not, when the overwhelming majority of the numbers ... Finding the square root is not ... > multiple primes but apparently the table driven method is usually ... If a religion is defined to be a system of ideas that contains unprovable ...
(sci.math)